1999
DOI: 10.1099/13500872-145-6-1453
|View full text |Cite
|
Sign up to set email alerts
|

Geminivirus-related extrachromosomal DNAs of the X-clade phytoplasmas share high sequence similarity

Abstract: fur Land-und Forstwi rtschaft, I nstit ut fur Pf I a n ze nsc h u t z i m Obstba u, Dossenheim, Germany Pathology, University of Georgia, Griffin, Georgia Southern blot hybridization analysis revealed that the extrachromosomal DNAs (EC-DNAs) associated with Vaccinium witches' broom (VAC) and walnut witches' broom phytoplasmas and various strains of the Italian clover phyllody phytoplasma (ICPh) were highly homologous among themselves but distinct from EC-DNAs of aster yellows related phytoplasmas occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…An extrachromosomal DNA found in SCWL phytoplasma (Nakashima & Hayashi, 1997) and a plasmid, pOYW1, found in OY phytoplasma (Kuboyama et al, 1998) were also reported to be extremely AT-rich. Rekab et al (1999) reported geminivirus-related extrachromosomal DNA from an X-clade phytoplasma. Although they only reported a partial sequence, their ORFB was highly homologous to the C-terminal region of geminivirus replication proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An extrachromosomal DNA found in SCWL phytoplasma (Nakashima & Hayashi, 1997) and a plasmid, pOYW1, found in OY phytoplasma (Kuboyama et al, 1998) were also reported to be extremely AT-rich. Rekab et al (1999) reported geminivirus-related extrachromosomal DNA from an X-clade phytoplasma. Although they only reported a partial sequence, their ORFB was highly homologous to the C-terminal region of geminivirus replication proteins.…”
Section: Discussionmentioning
confidence: 99%
“…An overall similarity between a protein encoded by ORF1 and a Rep protein of Tomato golden mosaic virus (TGMV), a geminivirus, is 66 %. Homologous deduced proteins were also reported for the extrachromosomal DNA from SCWL and VAC phytoplasmas (Rekab et al, 1999 ;Nakashima & Hayashi, 1997). Some of these proteins are aligned in Fig.…”
Section: Ecoyw1 Encodes a Homologue Of Geminivirus Replication Proteimentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, environments that allow frequent, multiple interactions between donor and recipient organisms favor high levels of HGT. Some examples include aquatic environments (Audic et al, 2007;Jiang and Paul, 1998), biofilms (Hendrickx et al, 2003;Sørensen et al, 2005), the human gut (Kurokawa et al, 2007;Xu et al, 2007) and cells co-infected by viruses or bacteria (Abbot et al, 2007;Rekab et al, 1999;Worobey and Holmes, 1999).…”
Section: Ecological Relationship Between Donor and Recipient Organismmentioning
confidence: 99%